2022
DOI: 10.3389/fneur.2022.947976
|View full text |Cite
|
Sign up to set email alerts
|

Nomogram for predicting traumatic subdural effusion after mild traumatic brain injury

Abstract: ObjectiveTraumatic subdural effusion (TSE) is a common complication of traumatic brain injury (TBI). This study aimed to determine the risk factors associated with subdural effusion and to propose a nomogram to predict the risk of TSE in patients with mild TBI.MethodsWe retrospectively analyzed 120 patients with mild TBI between January 2015 and December 2020 at the Third People's Hospital of Hefei. The risk factors of TSE were selected using univariate and multivariable logistic regression analysis. A nomogra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…Age plays a crucial role in determining the prognosis of various diseases (13)(14)(15). After adjusting for multiple factors in our analysis, older age was found to be an independent prognostic factor, .…”
Section: Discussionmentioning
confidence: 65%
“…Age plays a crucial role in determining the prognosis of various diseases (13)(14)(15). After adjusting for multiple factors in our analysis, older age was found to be an independent prognostic factor, .…”
Section: Discussionmentioning
confidence: 65%
“…A deterministic linkage dataset study in 2016 found that falling was Belgium's predominant cause of injury. Road safety and aging patients with TBI have increased recently, reducing transport-related TBI mortality and causing a shift in the health care system ( 1 , 6 , 7 ). Over the past two decades, significant advancements have been made in managing severe TBI both surgically and medically ( 8 ).…”
Section: Introductionmentioning
confidence: 99%